A contribuição da auditoria com a melhoria contínua de controle interno para minimização de riscos de fraudes nas organizações - Silva, Jeovan Lourenço da (2014)
This work includes exploratory and descriptive nature of the performance audit to continuous improvement of internal control to minimize risks of fraud in organizations aiming to provide a theoretical overview of the concepts of audit and risk, internal control, compliance and fraud specific objectives which relate to audit who uses methodologies for assessing the risks inherent to the activities of the company, addressing generic issues and their relationship to the internal control environment of enterprises, and then discuss the topic through the presentation of its phases and dimensions. This reference is directed to understanding the concepts of auditing and the difference between internal and external audit and the quality of audit work that can be measured. The main results refer reflection of the challenges of the audit to assist the internal control environment in order to decrease risks of fraud in companies with his work and methodology applied continuously, the need for accurate and reliable information for decision making and the relevance to that Audit has synergy with the Senior Management. Thus, the internal control environment and specializes certifies that its professionals have training to manage the major risks that the company is subject. The main gain is associated with the continuous improvement of internal control which should be incorporated into the management and culture of the organization